Impact of an extended orientation program on academic performance and retention - Lehning, Emily M. (Kansas State University, 2008)
This study investigated the impact of an extended orientation program, Wildcat Warm-up, on academic performance and retention. The study sought to quantify differences between students who participated in the program and those who did not attend in terms of grade point average and retention to sophomore year. Participants in the study were all domestic, full-time, freshmen undergraduate students enrolled at the institution in the fall semester (2004 to 2007). This study sought to provide descriptive and predictability data by comparing two groups of students. One group consisted of participants in Wildcat Warm-up while the second was a comparison group matched on ACT composite score, residency status, and gender. Institutional data were analyzed, including student self-report record information, institutionally generated grade reports from the end of each semester, and enrollment information. The participant group and comparison group were analyzed using descriptive statistics. The first two research questions provided a preliminary analysis of the overall impact of the extended orientation on the two measures identified for the study: freshman grade point averages and retention. The first research question and hypothesis were explored with a two-group independent samples Chi-square test with a dichotomous response variable. The second research question and hypothesis were explored with an analysis of variance (one-way ANOVA) for both first and second semester grade point averages. The third research question and remaining hypotheses were explored through a logistic regression analysis using the forward stepwise method. This study found there was a relationship between retention to sophomore year and Wildcat Warm-up participation and slight significant differences between first semester grade point averages for the two groups. In both cases, the strength of the association was small, but significant. The logistic regression analysis allowed for the creation of odds ratios for the predictor variables of the study where it was discovered when all other variables remain constant, the odds of a Wildcat Warm-up participant being retained from freshman to sophomore year were 31% higher than for a non-participant. While statistical significance was found, practical significance considerations did not allow much, if any of the variance, to be attributed to Wildcat Warm-up participation.
Keywords: College student retention; College orientation programs; Education, Higher (0745)